The best times to call in a mobile phone survey - Vicente, P. (International Journal of Market Research, 2015)
Establishing contact with the sample units is an important part of the survey response process, and an efficient calling schedule is critical to achieve high response rates. The rapid increase in mobile phone ownership has triggered the interest of marketing researchers in the use of mobile phones for collecting survey data about consumers. Mobile phone surveys may favour establishing contact with sample units since the mobile phone is a personal device carried at all times, thus making the person permanently contactable. This paper aims to identify the best times to call in a mobile phone survey by investigating the influence of the day and time of the call on the likelihood of establishing contact and obtaining an interview. A three-level ranking of calling periods, based on call efficiency, is proposed. Outcomes also revealed that the level of efficiency of calling periods is not dissociated from respondents’ socio-demographic characteristics, namely in terms of age and region of residence.